Journal of Evidenced-Based Psychotherapies, Vol. 24, Special Issue - DAVID, Oana Alexandra (Presa Universitară Clujeană, 2024)
Journal of Evidence-Based Psychotherapies (JEBP) is publishing in conjunction with the European Association for Behavioural and Cognitive Therapies (EABCT) the Special Issue dedicated to the main theme of EABCT’s 2022 Annual Congress in Barcelona – RE-thinking CBT: providing strategies for a new way of living. Authors of keynotes, symposium contributions, open papers and posters accepted for presentation at the conference and focused on investigating innovative CBT approaches and techniques were invited to submit to this Special Issue. Thus, our purpose for this special issue is to bring into the spotlight new developments in the field of CBT that can be effective in approaching current global concerns in terms of mental health.